2019
DOI: 10.1002/slct.201903256
|View full text |Cite
|
Sign up to set email alerts
|

A Non‐Noble Monometallic Catalyst Derived from Cu–MOFs for Highly Selective Hydrogenation of 5‐Hydroxymethylfurfural to 2,5‐Dimethylfuran

Abstract: Selective hydrogenation of biomass 5-Hydroxymethylfurfural (HMF) to 2, 5-dimethylfuran (DMF) which is a suitable candidate for liquid fuel has been widely concerned. Developing efficient and economic catalysts for the hydrogenation of HMF to DMF under mild conditions is a crucial issue. Here series monometallic Cu-based catalysts were synthesized from controlled thermolysis of Cu-BTC metal-organic frameworks and characterized by TG, N 2 adsorption-desorption, XRD, XPS, SEM, TEM, and H 2 -TPR techniques. The Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Previous studies have reported that Cu + species play an important role in the hydrogenation of HMF. 29 , 43 , 44 Therefore, in this study on a bimetallic catalyst, the pyrolysis temperature of 750 °C was used for the catalyst preparation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that Cu + species play an important role in the hydrogenation of HMF. 29 , 43 , 44 Therefore, in this study on a bimetallic catalyst, the pyrolysis temperature of 750 °C was used for the catalyst preparation.…”
Section: Resultsmentioning
confidence: 99%
“…The monometallic catalyst achieved 100% HMF conversion and a 92% DMF yield, but the reaction required a temperature of 180 °C and a time of 4 h. However, our previous research has proved that the activity of the monometallic catalyst significantly decreases after a reaction. 29 …”
Section: Resultsmentioning
confidence: 99%
“…[33] Zhang et al used 3 MPa H 2 under CuO x @C catalyst to completely convert HMF and obtain a DMF yield of 92%. [34] Although hydrogen has a wide range of applications, which is easy to decompose and activate, the high transportation cost, flammable and explosive risk, and low solubility in organic solvents make it difficult to use. [32,[35][36][37] Therefore, researchers hope to find a safe and effective hydrogen source to replace H 2 , among which the most studied hydrogen sources at present mainly include formic acid and alcohol.…”
Section: Hydrogen Donormentioning
confidence: 99%
“…Since their emergence, MOFs have attracted intensive attention as functional materials in hydrogen storage, [2–3] molecular recognition, [4] gas adsorption and separation, [5] selective catalyst, [6] and so on. For example, CuBTC and CuBTC‐derived composite materials are widely applied in the adsorption and removal of poluttant, [7–8] and Cu‐based organic reaction catalysts [9–11] . Recently, MOFs and their derivatives are investigated as active materials for electrochemical applications such as batteries, [12] supercapacitors, [13] and electrocatalysts [14] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, CuBTC and CuBTC-derived composite materials are widely applied in the adsorption and removal of poluttant, [7][8] and Cu-based organic reaction catalysts. [9][10][11] Recently, MOFs and their derivatives are investigated as active materials for electrochemical applications such as batteries, [12] supercapacitors, [13] and electrocatalysts. [14] The large specific surface area of MOFs is conducive to electrochemical reactions, and transition metal ions with multiple valence and organic ligands can provide abundant active sites for the chemical reaction.…”
Section: Introductionmentioning
confidence: 99%